PBB DAN KONFLIK DI MAGHREB: Inefektivitas United Nations Mission For The Referendum In Sahara (MINURSO) Terkait Penyelesaian Konflik Di Sahara Barat Antara Kerajaan Maroko Dan Frente Popular De Liberación De Saguía El Hamra Y Río De Oro (Front POLISARIO) - Arlan Faris (2023)
The Western Sahara conflict between the Front Polisario and Morocco has been ongoing for decades. In an effort to facilitate a peaceful resolution to the conflict, the United Nations (UN) established the United Nations Mission for the Referendum in Western Sahara (MINURSO) in 1991, aimed at monitoring the ceasefire between the two parties, organizing and overseeing a referendum for the people of Western Sahara to determine the political status of the region. The researcher adopts an explanatory research method with a qualitative approach, and the data collection method employed is a literature review. This research aims to explore the main mandate and role of MINURSO in the conflict between Morocco and Western Sahara, while analyzing the factors contributing to the ineffectiveness of MINURSO in the Western Sahara and Morocco conflict. These factors include political barriers and divergent perspectives on the Western Sahara region held by both parties, which subsequently affect MINURSO's performance in fulfilling its mandate.